An Information Systems Study on TRENDS, Inc. - Alampay, Erwin G.; Gan, Kerstin; Lacanaria, Sofia (Diliman, Quezon City College of Engineering, 1991)
TOTAL RESEARCH NEEDS, INC. (TRENDS), was founded in May 1980 by three women, Mercedes R. Abad, Aurora D. Caro, and Lourdes Villanueva, in pursuit of an ideal that Is TRENDS today. Registered as a corporation, April 1980, it has grown over the years, expanded its services, including qualitative interviews (focus group discussion) and developed a large clientele who continuously call on it for research needs. On August 15, 1991, TRENDS linked up with MBL-Asia Pacific Ltd., thus becoming member of the MBL group of companies worldwide. The company currently has over 500 interviewers stationed all over the country.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 154 : Information Systems I
Keywords: TOTAL RESEARCH NEEDS, INC. (TRENDS); Research teams; Information resources management